Dynamic Observation of Lung Nodules on Chest CT Before Diagnosis of Early Lung Cancer - Du, Qiaodan; Peng, Jia; Wang, Xiuyu; Ji, MingFang; Liao, Yuting; Tang, Binghang (Frontiers in Oncology, 2022)
Objective: Early recognition and diagnosis of lung cancer can help improve the prognosis of patients. However, the imaging of early lung nodules is not yet fully clear. To understand the early imaging signs of lung cancer malignant nodules, the changes of the lung nodules before diagnosis were dynamic observed and analyzed. Materials and Methods: This retrospective study observed dynamic changes of lung nodules before pathologically confirm with consecutive regular chest CT physical examination from January 2003 to December 2018. At least 3 follow-up CT scans were performed in all cases, and the interval between each follow-up was about one year. The size, density and morphological signs of the nodules were evaluated based on the CT axial image and a reverse line chart or scatter plot with the diagnosis time as coordinate origin was constructed. Results: A total of 55 lung nodules in 53 patients (mean age, 58.40 years ±11.43 [standard deviation]; 20 women) were accessed. The follow-up time was 5.96±2.68 years. The average diameter in maximum slice of the lesion at baseline and last scan were 6.83±2.92 mm and 16.65±7.34 mm, respectively. According to the reverse line chart, the nodule growth curve segments within 4 years from the last scan showed an ascending shape, and beyond 4 years showed a flat shape. There are 90.9% (50/55) GGN and 9.1% (5/55) SN when the lesion first appears; and 21.8% (12/55) GGN, 38.2% (21/55) PSN and 40% (22/55) SN in the last scan. There are 12.7% (7/55) and 98.2% (54/55) nodules had poor morphological signs at baseline and last scan, respectively. Conclusion: At the time node close to the diagnosis, the growth curve showed an upward pattern; the proportion of PSN and SN rose as the main density types; and the appearance of poor morphological signs of nodules increased.